POLA DERMATOM PADA PASIEN HERPES ZOSTER DI POLI KESEHATAN KULIT & KELAMIN RSUD DR. SOETOMO SURABAYA TAHUN 2012-2014 - Dara Sabrina, NIM011211133054 (2016)
Introduction: Herpes zoster is a disease caused by reactivation of varicella zoster virus which dormant inside patients who had been infected and cured from varicella before. Objective: The aim of this study is to know about dermatome pattern and charcteristics of herpes zoster patients in Dermatology Department of RSUD Dr. Soetomo Surabaya during 2012-2014. Methods: This was a retrospective study using medical records of herpes zoster patients in Dermatology Department of RSUD Dr. Soetomo Surabaya during 2012-2014. This study used both descriptive and analitic studies. There were 138 samples of herpes zoster patients with no complications. Other characteristics collected are sex, age, education, domicile, symptoms, and other underlying diseases history. Results: Herpes zoster are most commonly found in women, within the age range of 51-60 years old, symptoms were pain and burning sensation around lesion, mostly on the left side of body (40,58%), with the dermatome of thoracal region (41,30%), colli/auricula/facial region (18,84%), and abdomen/pelvic region (13,04%). The efflorescence were grouped vesicles (37,2%). Underlying disease mostly were varicella (53,49%), hypertension (13,95%), and diabetes mellitus (11,62%). After correlation tests were done, results show that there were no correlations between dermatome location and sex, symptoms, or underlying diseases, as well as the correlations between efflorescence and age nor sex. Although correlation between dermatome location and hypertension was found. Conclusion: Dermatome location was mostly found in thoracic region, on the left side of body, and efflorescence were grouped vesicles. Patients commonly were women, around 51-60 years old, complained about pain and burning sensation around lesion, and had varicella before. Keywords: herpes zoster, dermatome, location, side, efflorescence, sex, age, symptoms, underlying disease